2018
DOI: 10.1080/14756366.2018.1436053
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship investigation of tertiary amine derivatives of cinnamic acid as acetylcholinesterase and butyrylcholinesterase inhibitors: compared with that of phenylpropionic acid, sorbic acid and hexanoic acid

Abstract: In the present investigation, 48 new tertiary amine derivatives of cinnamic acid, phenylpropionic acid, sorbic acid and hexanoic acid (4d–6g, 10d–12g, 16d–18g and 22d–24g) were designed, synthesized and evaluated for the effect on AChE and BChE in vitro. The results revealed that the alteration of aminoalkyl types and substituted positions markedly influences the effects in inhibiting AChE. Almost of all cinnamic acid derivatives had the most potent inhibitory activity than that of other acid derivatives with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Compound 5 has been identified as a critical pharmacophore for AD treatment. Numerous studies have reported cinnamic acid derivative hybrids with quinoline [ 68 ], tryptamine [ 69 ], tertiary amine [ 70 ], tacrine [ 71 ], memantine [ 72 ], donepezil [ 73 ], and rivastigmine [ 74 ]. A tacrine and N-benzyl pyridinium hybrid with cinnamic acid exhibited a considerable improvement in AChE and BchE inhibition at the nanomolar level [ 71 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 5 has been identified as a critical pharmacophore for AD treatment. Numerous studies have reported cinnamic acid derivative hybrids with quinoline [ 68 ], tryptamine [ 69 ], tertiary amine [ 70 ], tacrine [ 71 ], memantine [ 72 ], donepezil [ 73 ], and rivastigmine [ 74 ]. A tacrine and N-benzyl pyridinium hybrid with cinnamic acid exhibited a considerable improvement in AChE and BchE inhibition at the nanomolar level [ 71 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 3a–3f were synthesized according to previous reported method (Gao et al, a). Halogen‐substituted cinnamic acid (2‐,3‐,or 4‐fluoro or chlorine cinnamic acid, 10 mmol), dichloromethane (30 mL) and a small amount of dimethylformamide (DMF) were added into the flask, followed by the addition of oxalyl chloride (2.55 mL, 30 mmol) drop by drop.…”
Section: Methodsmentioning
confidence: 99%
“…Substitution of different groups in basic skeleton of hispolon especially in aromatic phenyl ring played an excellent role in enhancing the biological activity. For example placement of methoxy group ( -OCH 3 ) in phenyl ring increase the cytotoxicity but in comparison, the presence of hydroxyl ( -OH ) group decrease the cytotoxicity and this has been supposed to be due to greater lipocity of methoxy (- OCH 3 ) as compared to hydroxyl ( OH ) ( Bisogno et al, 2007 ; Gaoa et al, 2018 ; Rossia et al, 2019 ). Moreover, it has been observed that the position of substitution on hispolon skeleton also played a crucial role in enhancing its activity as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). It means that unsaturation or olefininc double bond and aromatic ring are very important in enhancing the activity ( Gaoa et al, 2018 ; Ley et al, 2019 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%